RESPONS PERTUMBUHAN DAN PRODUKSI TANAMAN MELON (Cucumis Melo - Paian Simanungkalit; Jasmani Ginting Jasmani Ginting; Toga Simanungkalit2 Toga Simanungkalit2 (Universitas Sumatera Utara, 2013)
Growth Respons and Melon (Cucumis melo L.) production toward NPK fertilizer distribution and fruit prunning. The aim this result are to know the combinations of NPK fertilizer and the right fruit pruning for growth and production melon. Which is held in local farm on Tangga Batu Village, Tiga Juhar Subdistrict, Deli serdang regency with a height 100 meter of above sea level on May until August 2012 by using Randomized Block Design with two factorials which is control, NPK fertilizer and fruit prunning. The parameter observed were plant height, leaf quantity, male and female flowers ratio, production per plant, production per plot, persentase of grade A, persentase of grade B, and persentase of grade C. The result showed that annorganic fertilizer (NPK) and fruit prunning show significant effect on the parameter plant height, leaf quantity, production per plant and plot production. Key words : Melon, NPK fertilizer, fruit pruning